Promoting Religious and Moral Values in Early Childhood: A Quasi-Experimental Study of Multisensory Five Magic Words Habituation - Yusrafiddin; Cicih Murniasih; Juhana; Md. Rosli Ismail (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2026)
Religious and moral values constitute an important domain of early childhood development because they shape children’s respect, empathy, gratitude, responsibility, and self-regulation in everyday social interaction. However, young children require concrete, repeated, and socially meaningful experiences to translate moral values into observable behaviour. This study examined the effectiveness of multisensory Five Magic Words habituation in promoting polite behaviour among children aged 5 to 6 years. A quasi-experimental non-equivalent control group design was employed involving 96 children from early childhood education institutions. The experimental group participated in a three-week intervention combining visual, auditory, tactile, and kinaesthetic activities with repeated practice of greetings, “please,” “thank you,” “sorry,” and asking permission, while the control group received conventional religious and moral value learning. Data were collected using an authentic observation rubric that assessed children’s polite behaviour as an observable indicator of religious and moral value development. Because the data were not normally distributed, the Mann-Whitney U test was used to compare post-test scores between groups. The findings showed a statistically significant difference between the experimental and control groups (U = 1755.50, Z = -2.653, p = .008), with a small-to-moderate practical effect (r = .26). The study contributes globally to early childhood moral education by offering a behaviour-based approach for linking multisensory learning, politeness habituation, and observable moral behaviour. Practically, the findings imply that teachers can integrate polite language routines into sensory-rich classroom activities. However, the study is limited by its short intervention period, quasi-experimental design, and focus on observable behaviour rather than long-term value internalization.